1997
DOI: 10.1126/science.277.5326.663
|View full text |Cite
|
Sign up to set email alerts
|

An Advective-Reflective Conceptual Model for the Oscillatory Nature of the ENSO

Abstract: um hexafluorophosphate solut~ons, using freshly dstilled tetrahydrofuran or methyene chloride. A soutons were prepared under an atmosphere of nitrogen and degassed completely before injecton into the SEC cell. Blank reference solut~ons contalnng 0.1 M tetra-n-butyl ammonlum hexafluorophosphate were used for the Fourer transform R solvent subtractons. A Princeton Appl~ed Research (PAR) model 175 Unversal Programmer w~th a PAR model 176 Current Follower were used to effect and monitor thn-ayer bulk eectroyses. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
199
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(219 citation statements)
references
References 20 publications
15
199
0
5
Order By: Relevance
“…Note that the two processes can be closely linked, because of the geostrophic balance between the meridional gradient of the thermocline depth, and the zonal current. The delayed oscillator theory (Battisti and Hirst, 1989), and the recharge oscillator theory (Jin, 1996(Jin, , 1997a, had mentioned that the vertical thermal flux by mean upwelling associated with the thermocline depth, is a major contributor to the phase transition of the ENSO.On the other hand, the role of the advection of the mean SST by the anomalous zonal current has been stressed by Picaut et al (1996Picaut et al ( ,1997. In the study of Jin and An (1999) and this study, it is clearly demonstrated that the nonequilibrium adjustment of the tonal mean thermocline depth anomaly to the wind stress anomalies, acts to favor the transition of the ENSO through the two advectioe thermal processes, including the thermocline and tonal advection feedbacks.…”
Section: Flux Form Of the Sst Budgetmentioning
confidence: 90%
See 1 more Smart Citation
“…Note that the two processes can be closely linked, because of the geostrophic balance between the meridional gradient of the thermocline depth, and the zonal current. The delayed oscillator theory (Battisti and Hirst, 1989), and the recharge oscillator theory (Jin, 1996(Jin, , 1997a, had mentioned that the vertical thermal flux by mean upwelling associated with the thermocline depth, is a major contributor to the phase transition of the ENSO.On the other hand, the role of the advection of the mean SST by the anomalous zonal current has been stressed by Picaut et al (1996Picaut et al ( ,1997. In the study of Jin and An (1999) and this study, it is clearly demonstrated that the nonequilibrium adjustment of the tonal mean thermocline depth anomaly to the wind stress anomalies, acts to favor the transition of the ENSO through the two advectioe thermal processes, including the thermocline and tonal advection feedbacks.…”
Section: Flux Form Of the Sst Budgetmentioning
confidence: 90%
“…This process is referred to as thermocline feedback. Picaut and his colleagues (Picaut and Delcroix, 1995;Picaut et al, 1996Picaut et al, , 1997Delcroix and Picaut, 1998) through the observational work, stressed the importance of the advection of the mean SST by anomalous tonal current in the phase transition and growth of the ENSO. This process is referred to as zonal advection feedback.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a strong EN event implies strong discharge and subsequent low heat content with high probability (Fig. 11), due to the meridional displacement of zonal wind anomalies (Vecchi and Harrison 2006;McGregor et al 2012), which, together with zonal advection by reflected Rossby waves in the eastern equatorial Pacific (Picaut et al 1997;Dewitte et al 2003), leads to the termination of EN and the onset of a central Pacific LN (Fig. 4a; Vecchi and Harrison 2006;Kug et al 2010).…”
Section: Predictors and Triggering Of Strong El Niñomentioning
confidence: 99%
“…The El Niño and Southern Oscillation (ENSO), as one of the most prominent climate phenomena in the equatorial Pacific, has been extensively studied in the past decades (e.g., Suarez and Schopf 1988;Weisberg and Wang 1997;Jin 1997;Picaut et al 1997). In the western half of the equatorial Pacific, ENSO is seen as a zonal displacement of the warm ([28°C) pool, eastward during El Niño and westward during La Niña.…”
Section: Introductionmentioning
confidence: 99%